Lack of mitochondrial complex I assembly factor NDUFAF2 results in a distinctive infantile-onset brainstem neurodegenerative disease with early lethality - Firas Abu Hanna; Yoav Zehavi; Eran Cohen-Barak; Morad Khayat; Nasim Warwar; Roni Shreter; Richard J. Rodenburg; Ronen Spiegel (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Congenital disorders of the mitochondrial respiratory chain are a heterogeneous group of inborn errors of metabolism. Among them, NADH:ubiquinone oxidoreductase (complex I, CI) deficiency is the most common. Biallelic pathogenic variants in NDUFAF2, encoding the nuclear assembly CI factor NDUFAF2, were initially reported to cause progressive encephalopathy beginning in infancy. Since the initial report in 2005, less than a dozen patients with NDUFAF2-related disease have been reported. Methods Clinical, biochemical, and neuroradiological features of four new patients residing in Northern Israel were collected during 2016–2022 at Emek Medical Center. Enzymatic activities of the five respiratory-chain complexes were determined in isolated fibroblast mitochondria by spectrophotometric methods. Western blot analyses were conducted with anti-human NDUFAF2 antibody; antibody against the mitochondrial marker VDAC1 was used as a loading control. Genetic studies were performed by chromosome microarray analysis using Affymetrix CytoScan 750 K arrays. Results All four patients presented with infantile-onset growth retardation, ophthalmological impairments with nystagmus, strabismus (starting between 5 and 9 months), and further progressed to life-threatening episodes of apnea usually triggered by trivial febrile illnesses (between 10 and 18 months) with gradual loss of acquired developmental milestones (3 of 4 patients). Serial magnetic-resonance imaging studies in two of the four patients showed a progressive pattern of abnormal T2-weighted hyperintense signals involving primarily the brainstem, the upper cervical cord, and later, the basal ganglia and thalami. Magnetic-resonance spectroscopy in one patient showed an increased lactate peak. Disease progression was marked by ventilatory dependency and early lethality. 3 of the 4 patients tested, harbored a homozygous 142-kb partial interstitial deletion that omits exons 2–4 of NDUFAF2. Mitochondrial CI activity was significantly decreased in the only patient tested. Western blot analysis disclosed the absence of NDUFAF2 protein compared to normal controls. In addition, we reviewed all 10 previously reported NDUFAF2-deficient cases to better characterize the disease. Conclusions Biallelic loss-of-function mutations in NDUFAF2 result in a distinctive phenotype in the spectrum of Leigh syndrome with clinical and neuroradiological features that are primarily attributed to progressive brainstem damage.